Relationship between visceral adipose tissue and genetic mutations (VHL and KDM5C) in clear cell renal cell carcinoma - Greco, Federico; Mallio, Carlo Augusto (Radiologia medica, 2021)
Background The sequencing of the renal cell carcinoma (RCC) genome has detected several mutations with prognostic meaning. The association between visceral adipose tissue (VAT) and clear cell renal cell carcinoma (ccRCC) is well known. The relationship among abdominal adipose tissue distribution and ccRCC-VHL and KDM5C genetic mutations is, to the knowledge of the authors, not known. Methods In this retrospective study, we enrolled 97 Caucasian male patients divided into three groups: the control group ( n = 35), the ccRCC-VHL group ( n = 52) composed of ccRCC patients with VHL mutations and ccRCC-KDM5C group ( n = 10) composed of ccRCC patients with KDM5C mutation. Total adipose tissue (TAT) area, VAT area and subcutaneous adipose tissue (SAT) area were measured in the groups. VAT/SAT ratio was calculated for each subject. Results Statistically significant differences between ccRCC-KDM5C group and ccRCC-VHL group were obtained for TAT area ( p < 0.05), VAT area ( p < 0.05) and VAT/SAT ratio ( p < 0.05); between ccRCC-VHL group and control group for TAT area ( p < 0.001) and VAT area ( p < 0.01); and between ccRCC-KDM5C group and control group for TAT area ( p < 0.0001), VAT area ( p < 0.0001) and SAT area ( p < 0.01). Conclusions This study demonstrates for the first time an increased amount of TAT, especially VAT, in the ccRCC-VHL and ccRCC-KDM5C groups. The effect was greater for the ccRCC-KDM5C group.